2020
DOI: 10.1155/2020/8814626
|View full text |Cite
|
Sign up to set email alerts
|

Influence of High Water Pressure on Static and Dynamic Compressive Strength of Concrete

Abstract: In this paper, an experimental study was conducted on the influence of water pressure on concrete strength. Specimens were put in a self-designed device, applying 0–4 MPa water pressure on concrete, and then taken out for both static and dynamic compressive tests. Results showed that high water pressure caused inevitable damage to concrete, leading to 13.4% reduction in strength under 4 MPa water pressure. Specimens with lower strength grade were damaged more severely while under the same water pressure. Also,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 25 publications
(28 reference statements)
2
15
0
Order By: Relevance
“…In particular, the laboratory study [ 6 ] showed that samples of mortar 10 cm thick are saturated with water up to 80% within the first day of being in the vessel. This estimate is confirmed by other experimental studies, which indicate that close to full saturation of laboratory concrete samples with water or aqueous solution is achieved within 1–3 days [ 7 , 8 , 9 ]. The surface layers of massive concrete structures in a water or water-saturated environment can therefore be completely saturated with water to a depth of at least 10 1 cm and higher.…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…In particular, the laboratory study [ 6 ] showed that samples of mortar 10 cm thick are saturated with water up to 80% within the first day of being in the vessel. This estimate is confirmed by other experimental studies, which indicate that close to full saturation of laboratory concrete samples with water or aqueous solution is achieved within 1–3 days [ 7 , 8 , 9 ]. The surface layers of massive concrete structures in a water or water-saturated environment can therefore be completely saturated with water to a depth of at least 10 1 cm and higher.…”
Section: Introductionsupporting
confidence: 87%
“…This effect most clearly appears under compression, which is the typical type of stress state of elements of concrete constructions. Different experimental studies show that the compressive strength of concrete samples can decrease by 10–20 percent with an increase in water saturation [ 6 , 7 , 10 , 18 , 19 , 20 ]. Moreover, compression tests on water-saturated samples in a high water pressure device (at different values of water pressure) demonstrate an additional decrease in quasi-static strength by more than 10% with an increase in pore pressure from atmospheric value to several MPa [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have been conducted on the response of concrete to cyclic high water pressure, and the main concern has been on the mode of failure [ 23 , 26 , 32 , 33 , 34 , 35 ]. Chen et al [ 34 ] carried out a first dynamic mechanical experiment with water pressure on concrete, wherein loading was applied when the water pressure was steady and the saturation condition of the specimen was not clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Under low confining pressure, failure was caused by crack propagation parallel to the primary load direction; however, cracks became less frequent and oriented in a sidewise direction under higher confinement [ 26 , 35 ]. Zhou et al [ 32 ] concluded that the maximum reduction in static and dynamic compressive strength was 13.4% in testing under 4 MPa of water pressure. Given this limited understanding, further experiments on the effect of static and dynamic water pressure on concrete compressive strength are necessary that are not yet considered in the aforementioned literature, particularly considering deterioration related to the penetration of water into a specimen and migration within it.…”
Section: Introductionmentioning
confidence: 99%